1982
DOI: 10.1128/iai.36.2.720-729.1982
|View full text |Cite
|
Sign up to set email alerts
|

Murine respiratory mycoplasmosis in F344 and LEW rats: evolution of lesions and lung lymphoid cell populations

Abstract: By comparison of two rat strains, LEW and F344, which are known to differ in susceptibility to Mycoplasma pulmonis respiratory disease, it was shown that differences in lesion severity and progression were associated with changes in lung lymphocyte populations. Lung lesions in LEW rats developed earlier after infection, became more severe, and were characterized by continued proliferation of all classes of lymphoid cells, T lymphocytes, B lymphocytes, and plasma cells, throughout the 120-day observation period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 25 publications
(24 reference statements)
3
36
0
Order By: Relevance
“…Identification of a DNA inversion system in the M. pulmonis vsa locus M. pulmonis strain UAB 6510 is a respiratory pathogen of rats (Davis et aL, 1982) that served as the progenitor of the other strains used in this study. A description of the lineage and pertinent properties of these strains is provided in the Experimental procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of a DNA inversion system in the M. pulmonis vsa locus M. pulmonis strain UAB 6510 is a respiratory pathogen of rats (Davis et aL, 1982) that served as the progenitor of the other strains used in this study. A description of the lineage and pertinent properties of these strains is provided in the Experimental procedures.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, immune cells protect against experimental infection in genetically resistant F344 strain rats (2). It has been reported that there are differences in the responses of rat strains F344 and LEW (7,10,11) and various mouse strains (9,24) to infection with M. pulmonis. The differences in the relative importance of cellular and antibody-mediated mechanisms of resistance to M. pulmonis may have been related to strain (resistant versus susceptible) rather than species differences (14).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cells infiltrate lungs of rats and mice following M. pulmonis infection (4,8,11). A significant number of cells (about 50% in tissue sections) were morphologically indistinguishable from lymphocytes, which failed to stain with either Tor B-cell reagents, and were called null cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the Lewis strain this was characterized after 28 days by a variable acute inflammatory exudate in bronchi and bronchioles with focal bronchiectasis, inflammation and hyperplasia of the epithelium with a predominantly macrophage infiltration of the alveoli and alveolar walls. 65,143 These changes were associated with marked hyperplasia of the bronchus-associated lymphoid tissue (BALT), which extended down the airways and blood vessels towards the periphery of the lungs. Although the lymphoid hyperplasia was also found in inoculated Fischer 344 rats, it was less marked and accompanied by little or no mucopurulent exudate or active inflammation of the bronchial walls.…”
Section: Inflammation Found Spontaneously and Due To Infections And Imentioning
confidence: 99%
“…This disparity in response suggested that differences were related to the degree of lymphocyte activation in the two strains, an imbalance in regulation of lymphocyte proliferation in Lewis rats, or both. 143 Other studies have been conducted in both rats and mice infected with another important respiratory pathogen of laboratory rodents, the Sendai virus (parainfluenza type 1). Sequential studies showed that the initial damage to bronchial and bronchiolar epithelium is associated with polymorphonuclear and lymphocytic inflammation (bronchiolitis).…”
Section: Inflammation Found Spontaneously and Due To Infections And Imentioning
confidence: 99%